Aborted genital herpes simplex virus lesions: findings from a randomised controlled trial with valaciclovir. Issue 6 (1st December 2002) - Strand, A; Patel, R; Wulf, H C; Coates, K M
Abstract : Objectives: In prospective trials, episodic valaciclovir significantly increased the chance of preventing or aborting the development of painful vesicular genital herpes simplex virus (HSV) lesions compared with placebo. We explored the clinical outcome of aborted lesions and its association with early treatment in a study designed to compare 3 and 5 days' treatment with valaciclovir. Methods: In a randomised controlled trial, valaciclovir 500 mg twice daily for 3 or 5 days was initiated at the first symptoms of a genital herpes outbreak. The primary end point was length of episode with pain, HSV shedding, and aborted lesions secondary end points. The effect of time from symptom recognition to treatment initiation on aborted lesions was assessed in a post hoc analysis. Results: In 531 patients, no differences were observed between 3 and 5 days' treatment in episode duration (median 4.7 v 4.6 days), loss of pain/discomfort (2.8 v 3.0 days), or lesion healing (4.9 v 4.5 days). Vesicular lesions were aborted in 27% of patients treated for 3 days v 21% of patients receiving valaciclovir for 5 days. The odds of achieving an aborted episode were 1.93 (95% CI: 1.28 to 2.90) times higher for those initiating treatment with valaciclovir within 6 hours of first sign or symptom. Conclusions: There was no difference between 3 and 5 days' treatment in reducing episode duration or lesion abortion. Prompt treatment with valaciclovir can abort genital HSV reactivation episodes, preventing a vesicular outbreak. Maximum treatment benefit depends on prompt therapy after recognition of symptoms.